Community leadership - Einsiedel, Luz A.
Leadership in community organization (whether in a geographical and/or functional field) implies a conscious and persistent effort to bring about a development, alignment and mobilization of social welfare resources as well as to meet most effectively and efficiently the social welfare needs of the unit. This is likely to involve the necessity of bringing about the creation of new services and programs, the realignment and modification, and in some cases the termination of existing programs.
Keywords: Community leadership